Oncostatin M promotes excitotoxicity by inhibiting glutamate uptake in astrocytes: implications in HIV-associated neurotoxicity - Moidunny, Shamsudheen (J Neuroinflammation, 2016)
BACKGROUND: Elevated levels of oncostatin M (OSM), an interleukin-6 cytokine family member, have been observed in HIV-1-associated neurocognitive disorders (HAND) and Alzheimer’s disease. However, the function of OSM in these disease conditions is unclear. Since deficient glutamate uptake by astrocytes is instrumental in HAND-associated neurotoxicity, we hypothesized that OSM impairs glutamate uptake in astrocytes and thereby promotes neuronal excitotoxicity. METHODS: Primary cultures of mouse cortical astrocytes, neurons, microglia, and BV2 cell line were used. The expression of glutamate transporters (GLAST/EAAT1 and GLT-1/EAAT2) was investigated using real-time PCR and Western blot, and their activity was assessed by measuring (3)H-d-aspartate uptake. Neuronal toxicity was measured using the colorimetric MTT (3-(4,5-dimethylthiazol-2-yl-) 2,5-diphenyltetrazolium bromide) assay and immunocytochemistry. A chimeric HIV-1 that infects murine cells (EcoHIV/NL4-3-GFP virus (EcoHIV)) was used to investigate whether the virus induces OSM, OSM receptor (OSMR)-β, glycoprotein 130 (gp130), GLT-1, GLAST (mRNA and protein), and OSM release (ELISA) in cultured BV2 cells, primary microglia, or astrocytes. Statistical analyses of the data were performed using one-way ANOVA (to allow multiple comparisons) and two-tailed Student’s t test. RESULTS: OSM treatment (10 ng/mL) time-dependently reduced GLAST and GLT-1 expression and inhibited (3)H-d-aspartate uptake in cultured astrocytes in a concentration-dependent manner, an effect prevented by the Janus kinase (JAK)/signal transducers and activators of transcription (STAT)3 inhibitor AG490. Down-regulation of astrocytic glutamate transport by OSM resulted in NMDA receptor-dependent excitotoxicity in cortical neurons. Infection with EcoHIV induced OSM gene expression and protein release in BV2 cells and microglia, but not in astrocytes. Conversely, EcoHIV caused a fivefold increase in OSMR-β mRNA (but not gp130) and protein in astrocytes, but not in microglia, which did not express OSMR-β protein. Finally, astrocytic expression of GLAST gene was unaffected by EcoHIV, whereas GLT-1 mRNA was increased by twofold. CONCLUSIONS: We provide first evidence that activation of JAK/STAT3 signaling by OSM inhibits glutamate uptake in astrocytes, which results in neuronal excitotoxicity. Our findings with EcoHIV suggest that targeting OSMR-β signaling in astrocytes might alleviate HIV-1-associated excitotoxicity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-016-0613-8) contains supplementary material, which is available to authorized users.